Peculiarities of the Future Teachers Professional Identity and Proffesional Marginalism - Kochkrova, O. V. (Psychological Prospects Journal, 2012)
The future teachers professional marginalism as a breach of their professional pedagogical identity is considered in the article. It is underlined that professional marginalism and professional identity keep polar positions in the limits of professional society. The dynamics of evolution of the students-future teachers’ professional identity statuses is studied.